Manejo da irrigação e adubação nitrogenada no feijoeiro – cultivar BRS FC402 - COUTO, Caio Oliveira Pimenta; LOPES, Adriano da Silva; FRANCO, Jhonatan da Silva; KRAESKI, Marcos Jefferson (ANAIS DO ENIC, 2025)
-